Towards understanding the development and characteristics of under-expanded flash boiling jets. (August 2020) - Guo, Hengjie; Nocivelli, Lorenzo; Torelli, Roberto; Som, Sibendu
Highlights: The flow development of under-expanded flash boiling jets was investigated. Differences between flashing jets and frozen two-phase jets were revealed. Key factors determining the characteristics of flashing jets were discussed. Two flow choking mechanisms have been identified for flashing jets. Abstract: In this research, the n-hexane jets discharged from a straight channel were studied numerically to reveal the development and characteristics of under-expanded flashing jets. Firstly, the development of flash boiling jets was investigated and compared to that of two-phase jets without phase transition. It was shown that the two-phase jets without phase transition can be under-expanded only if the flow is choked. In contrast, flash boiling jets can be under-expanded whether or not the choked conditions are verified. Secondly, the factors affecting the flashing jet behaviors were discussed. The relaxation time in phase transition, the expansion ratio, and the injection pressure have been identified as three key factors determining the jet characteristics. With high enough expansion ratio and low enough relaxation time, the expansion was so strong that the flow became transonic and shock structures similar to those of under-expanded gaseous jets appeared near the orifice exit. Finally, two types of choking have been identified for flash boiling jets, i.e., vaporization-induced choking and expansion-induced choking. The former one is mainly ascribed to the vapor formation in the orifice which reduces the local speed of sound, while the latter one is due to the expansion of under-expanded two-phase flow and the resultant flow acceleration.